APLIKASI PENGELOLAAN DATA LABORATORIUM DI PDAM BANDARMASIH KOTA BANJARMASIN - Wagino Wagino (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
At PDAM Bandarmasih of Banjarmasin city, the laboratory division of data management system and report still use simple application. It is considered less effective and efficient in supporting the work productivity of employees in it, so it will take a little time in the process of data management laboratory, search data and provide information. From these problems raised the proposal to create a web-based application, in which it can perform the management of laboratory data. The methodology used in making this application is the programming language is PHP. for display using CSS and Jquery. Database using MySQL. Tools and Editor used are Xammp and Notepad ++. Supported by the availability of local internet network (intranet) in PDAM Bandarmasih Banjarmasin. This application is used as a media input, editing, and data deletion, data management with the Application of data management Laboratory PDAM Bandarmasih Banjarmasin City is expected to facilitate employees in managing laboratory data and data collection process so that the results of reporting data can be known easily, quickly and accurately . Keywords: PDAM Bandarmasih, Laboratory, Php, Css (Cascading Style Sheets), Xampp, MySql.